Immunohistochemical evaluation of neuronal dysfunction in paediatric patients with Hirschsprung’s disease and allied disorder - Bhatia, Yashika; Singh, Sunita; Rattan, Kamal Nain; Parmar, Padam; Ralli, Megha; Sen, Rajeev (International Journal of Research in Medical Sciences, 2018)
Background: Neonatal bowel obstruction may result due to defect in the intestine wall which may be classified as neuropathic, myopathic or idiopathic types according to the pathological changes observed. The present study was conducted between September 2014 to December 2015 with the aim to study histomorphological changes and evaluate the role of various IHC markers (calretinin, S-100, CD117) in Hirschsprung’s disease (HD) to assess neuronal dysfunction in these patients. Methods: Thirty cases with clinical suspicion of HD were included in our study. The tissue sections were processed and wax blocks were prepared. Histopathological diagnosis was established on routine H and E. Representative sections were further subjected to IHC staining with calretinin, CD117 and S-100 protein. A descriptive study was carried out. Chi-square was used with P-value less than 0.05 accepted as statistically significant. Results: Out of 30 cases with clinical suspicion of HD, 13 cases were diagnosed as HD, 10 as Non-HD motility disorder whereas 7 were without any definitive diagnosis. All the cases were subjected to IHC staining using calretinin. Out of 13 cases diagnosed as HD, 1 case showed presence of ganglion cell using calretinin. All 7 equivocal cases were accurately diagnosed by calretinin. Thus 12 cases were confirmed HD while 18 were diagnosed as Non HD motility disorder. On statistical analysis, sensitivity (92.3%) of calretinin was lower than specificity (100%). Nerve bundle hypertrophy was observed in 11 cases of HD and 9 cases of Non-HD motility disorder using S-100 as an IHC marker. CD117 was used to demonstrate altered density and distribution of ICCs was statistically significant in cases of Non-HD motility disorder. Conclusions: IHC is being widely used as a reliable adjunctive test in evaluation of motility disorders of bowel. In view of its ease and reproducibility, it can be routinely used, avoiding need for repeated biopsies, and delay in treatment.